1978
DOI: 10.1111/j.1471-4159.1978.tb10463.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO FORMATION OF POLYUNSATURATED FATTY ACIDS BY DESATURATION IN RAT BRAIN: SOME PROPERTIES OF THE ENZYMES IN DEVELOPING BRAIN AND COMPARISONS WITH LIVER1

Abstract: Abstract— In vitro desaturation of [1‐C14]linolenic, linoleic, oleic, and icosatrienoic acids was determined using homogenates and subcellular fractions of developing rat brain and liver. Linolenic, linoleic, and oleic acids were desaturated in the δ6‐position and activity was optimal in the presence of CoA, ATP, MgCl2, and NADH in a citrate‐phosphate buffer at pH 6.0. Icosatrienoic acid was desaturated in the δ5‐position with a much broader pH optimum. The unstable desaturation systems of brain were protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
39
1
5

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 21 publications
7
39
1
5
Order By: Relevance
“…It has been suggested that the brain receives much of its complement of DHA "preformed" from the circulation via the liver (33,34), although the rat brain, and especially the developing rat brain, has a substantial capacity for the synthesis of DHA from precursor molecules (35,36). Our results showed that DHA was formed from dietary EPA and accumulated in the brain to nearly the same extent as the DHA when fed directly in the diet.…”
mentioning
confidence: 46%
“…It has been suggested that the brain receives much of its complement of DHA "preformed" from the circulation via the liver (33,34), although the rat brain, and especially the developing rat brain, has a substantial capacity for the synthesis of DHA from precursor molecules (35,36). Our results showed that DHA was formed from dietary EPA and accumulated in the brain to nearly the same extent as the DHA when fed directly in the diet.…”
mentioning
confidence: 46%
“…In vitro preparation from brain and liver (Cook, 1978) showed that in the very young 10-day-old rats, conversion of 18:2n-6 and 18:3n-3 by A6-desaturation was much higher in brain than in liver. The A5-desaturation of 20:3n-6, although very low in brain, was also significantly higher than in liver.…”
Section: Dietary Sources Of Essential Fatty Acidsmentioning
confidence: 96%
“…Metabolic activity reflecting EFA elongation and desaturation in human subjects is found mainly in the liver, but also in the placenta, central nervous system, glial tissue and choroid plexus vasculature (Bourre et al 1997;Cook, 1978). Whole-body elongase and desaturase activity can be assessed in vivo using either 2 H-or 13 C-labelled EFA substrates, enabling the evaluation of product formation in plasma and tissue compartments.…”
mentioning
confidence: 99%